Strategies, Errors, and Challenges in Translating Culture-Specific Items in Chinese-English Literary Works : A Systematic Review - Qiufen, Wang; Amini, Mansour; Tan, Debbita Ai Lin (Jurnal Arbitrer, 2025)
In this paper, the Chinese to English literary translation of Culture-Specific Items (CSIs) published between 2019 and 2024 is analyzed. Different types of CSIs, such as idioms, historical references, proverbs, and culturally specific phrases, are among the most difficult items to translate because of their deep cultural meaning and the challenge in finding appropriate English equivalents. Although exploration of cultural factors and their translations has become increasingly popular, particularly in Translation Studies, systematic reviews of CSIs especially in Chinese to English literary contexts are limited. We employed a qualitative content analysis to synthesize the findings of 25 selected and refined articles. Among them, 18 were empirical articles, while seven were reviews, mainly focusing on the theoretical and conceptual features of CSIs, collected from Google Scholar, JSTOR, and PubMed databases. Three major themes were identified: (1) definitions and typologies of CSIs, (2) translation strategies, and (3) translation errors. We found that among the various strategies and procedures involved in translating CSIs, domestication, foreignization, annotation, adaptation, and literal translation were the most popular, each acknowledging their context-specific efficiencies and limitations. Furthermore, the identified translation errors included cultural misinterpretation, loss of style, omission, and loss of functionality. These errors could often hinder reader comprehension and negatively influence the narrative. Based on the findings, we recommend maintaining a balance between linguistic and cultural faithfulness, emphasizing genre sensitivity, recognizing the significance of translator visibility, and in-depth exploration of the context, and functional equivalence. Conducting empirical reception studies, in addition to further examination of genre representation, integration of human evaluation, and exploring the potential role of translation technology in translating cultural items could offer theoretical and practical guidance to literary translators dealing with cultural items.